Urgensi Literasi Media di Tengah Sinisme Antarsuku, Agama, Ras, dan Golongan - Zubaidi, Advan Navis (Jurnal Komunikasi Islam, 2018)
This article discusses the urgency of media literacy in addressing the framing of cynicism and conflict issues between tribes, religions, races and groups carried out by the mass media in Indonesia. Specifically, this study attempts to contribute the role of media literacy in minimizing cynicism between tribes, religions, races and groups. Through text studies, this article argues that literacy is considered as science. The more educated people, the more acquired knowledge will be. It means that when people receive more information from the mass media, they will certainly be wiser. Further, to raise public awareness, a systematic way through education, both formal and non-formal, is needed. Hence, harmonious human relations could be realized, regardless of ethnic status, race, and religious belief.